2017
DOI: 10.1007/s40800-017-0048-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotor Agitation Following Treatment with Hydroxychloroquine

Abstract: We describe the case of an elderly woman with elderly-onset rheumatoid arthritis, where the use of 4 mg/kg/day of hydroxychloroquine (HCQ) was followed by the onset of psychomotor agitation with marked physical and verbal violence towards her partner, including throwing objects at her partner. No disturbance in sleep and no anxiety, nervousness, or irritability had emerged before the onset of her psychomotor agitation. The disappearance of agitation following targeted pharmacologic intervention and HCQ interru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 24 publications
0
38
2
Order By: Relevance
“…Our results did not reveal a significant effect of HCQ treatment on working memory, but total exploration time was decreased after HCQ administration, which also suggests that the drugs increased anxiety. Previous human studies have reported that HCQ can induce anxiety-and depression symptoms (10,11), but no reports have shown that it impairs cognitive function. However, there have been only a few reports in humans, and there is a close relationship between cognitive impairment and psychiatric disorders (24).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our results did not reveal a significant effect of HCQ treatment on working memory, but total exploration time was decreased after HCQ administration, which also suggests that the drugs increased anxiety. Previous human studies have reported that HCQ can induce anxiety-and depression symptoms (10,11), but no reports have shown that it impairs cognitive function. However, there have been only a few reports in humans, and there is a close relationship between cognitive impairment and psychiatric disorders (24).…”
Section: Discussionmentioning
confidence: 98%
“…There have been reports of serious adverse effects related to HCQ, including retinopathy, QT interval prolongation, hypoglycemia, cardiomyopathy, neuropsychiatric effects and so on (7,8), and QT interval prolongation is the most closely monitored adverse effect in patients with SARS-COV-2. Less attention has been paid to the effects of HCQ on mental health, although multiple studies have reported severe psychiatric symptoms, including agitation, hallucinations, anxiety, depression, and suicidal ideation, in patients treated with HCQ or chloroquine (9)(10)(11)(12). However, whether these neuropsychiatric symptoms are caused by HCQ alone or by the interaction between HCQ and the disease is not well studied, possibly due to the limited number of reported cases.…”
Section: Introductionmentioning
confidence: 99%
“…For example, chloroquine and hydroxychloroquine, which were commonly used earlier in the pandemic, could potentially increase the likelihood of neurological disorders, especially in the elderly [114]. The use of hydroxychloroquine has been associated with neuropsychiatric manifestations including irritability, nervousness and psychosis, possibly by its ability to cross the BBB [115]. Corticosteroids, another common group of medications used to treat severe cases of COVID-19, have also been associated with psychiatric symptoms, especially when administered at high doses [116].…”
Section: Potential Neuropathological Effects Of Current Covid-19 Thermentioning
confidence: 99%
“…There are numerous side effects during HCQ therapy, some of which are favored according to predisposing or precipitant factors. Among these, cytochrome P450 3A4 inhibitors (such as indinavir, nelfinavir, ritonavir, clarithromycin, erythromycin, fluconazole, itraconazole, ketoconazole, amiodarone, cimetidine, diltiazem, and verapamil) may increase the half-life of HCQ, favoring its toxicity [31].…”
mentioning
confidence: 99%